THE HEAT STABILITY OF RADIATION CROSSLINKED OF BIONOLLE - Meri Suhartini; Fumio Yoshii; Naotsugu Nagasawa (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2004)
THE HEAT STABILITY OF RADIATION CROSSLINKED OF BIONOLLE. Bionolle with chemical names Poly(butylene succinate-co-adipate), Poly(butylene succinate) (PBS), were irradiated using electron beam (EB) in presence of five different polyfunctional monomers at ambient temperature. It was pointed out that the highest amount of gel fraction could be achieved when PBS wad blend with trimethallyl isocyanurate (TMAIC). It was obtained that crosslinked BS containing 1% of TMAIC produces higher gel fraction than that crosslinked PBS containing 2 or 3% TMAIC at dose of 50 kGy. The PBS containing 1% of TMAIC also has higher glass transition (Tg) than that of original PBS. It was observed that the presence of crosslinking bonds in irradiated PBS greatly improved its heat stability as well as diminished its ability to biodegradation. Accordingly, it can be concluded that crosslinked PBS in the presence of TMAIC has significantly improved heat resistant properties.